2015
DOI: 10.1111/jocn.12820
|View full text |Cite
|
Sign up to set email alerts
|

Promoting graded exercise as a part of multimodal treatment in patients diagnosed with stress‐related exhaustion

Abstract: Exercise can be successfully promoted as a part of multimodal treatment in patients with stress-related exhaustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 62 publications
0
16
0
1
Order By: Relevance
“…Hence, this may have counteracted fulfilling participation in the study. Obstacles to include additional exercise sessions in MMR was also confirmed in a previous study in which only 21% of patients with ED, who participated in MMR, chose to voluntary participate in an 18-week coached exercise program [ 39 ]. Another reason for the high dropout rate may be due to the training method and intensity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Hence, this may have counteracted fulfilling participation in the study. Obstacles to include additional exercise sessions in MMR was also confirmed in a previous study in which only 21% of patients with ED, who participated in MMR, chose to voluntary participate in an 18-week coached exercise program [ 39 ]. Another reason for the high dropout rate may be due to the training method and intensity.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the addition of aerobic training in our study, no significant differences could be detected in the psychological variables in the intervention group compared to the control group. Previous studies have shown that patients with ED participating in MMR where information on physical activity recommendation are included, also increase their levels of self-reported exercise [ 39 ]. Moreover, Lindegård et al [ 40 ] compared patients with ED who complied or not with physical activity recommendations and observed no differences between the groups in levels of burnout, depression and anxiety during a 12-months MMR intervention where all groups improved.…”
Section: Discussionmentioning
confidence: 99%
“… Ekkekakis et al (2008 , 2011 ) and Ekkekakis (2009) argued that physical activity per se might be an agreeable sensation, which, by nature, might lead to feelings of well-being and improved mood. From a psychological point of view, Knapen et al (2005 , 2015 ) argued that physical activity has the power to improve self-esteem, self-efficacy, feelings of pride and achievement, and stress-resistance [see also Gerber et al (2015a , b )]. While Knapen et al (2005 , 2015 ) attributed such improvements to longer lasting interventions, in the present study we were able to show that improved mood was observable after a single bout of exercise among inpatients with a broad variety of psychiatric diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, instructors should emphasize that improvements with regard to physical activity and fitness are exclusively related to patients’ efforts, hereby improving patients’ self-efficacy. Moreover, we posit that doses of exercise should be increased gradually in order to avoid feelings of failure and helplessness, which might be counterproductive in the long run 25. Such an approach is also mirrored in the behavioral analysis as proposed by Kanfer and Saslow 26.…”
mentioning
confidence: 99%